Health and work contexts of nursing professionals during the pandemic of COVID-19 - Silveira Silva, Lívia (2026)
Introduction: By performing and promoting practices that aim to improve health, the nursing team has assumed itself as a protagonist during  the COVID-19 pandemic. Therefore, the personal, professional, and family exposure is evident; the lack of personnel and occupational security, in addition to the consequences on the health and work contexts of these professionals. Objective: To analyze the health and work contexts of nursing professionals during the pandemic of COVID-19. Methodology: This is a mixed-method study that combines approaches through the concurrent incorporation strategy – QUAN(qual), conducted in Minas Gerais, Brazil, between August and December 2020. A script of questions was applied over the phone to 58 professional nurses, nursing technicians, and nursing assistants. The script included open and closed questions related to sociodemographic issues and health, work, and COVID-19 contexts and conditions. A descriptive quantitative analysis and thematic content analysis were performed. Results: The majority were women (93.1%) nursing technicians (69%). The 39.7% of the participants worked the night shift; the 58.6% reported experiencing violence at work and the 48.3% was diagnosed with mental disorders. The work contexts during the pandemic showed that there was a need for encouragement and professional evaluation; they also portrayed the relationships with the institutional factors, the work dynamics and the organization, the appropriate working conditions and the favorable interpersonal relationships. On the other hand, health contexts showed the relationship between interests, opportunities, routine, normality, hope and tenacity that would occur at the end of COVID-19. Conclusion: The pandemic of COVID-19 strengthened a critical, fearful, and insecure health and work context of the Brazilian nursing team, exacerbating the need for provisions, actions and policies that consider worker's health crucial for the organization of services.